2019
DOI: 10.3102/0162373719845653
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Engagement With Faculty and Staff to Facilitate Student Success: An Evaluation of a Parent Intervention

Abstract: Many low-income and first-generation students who enroll in college experience less desirable outcomes during their first year. Researchers have increasingly investigated the important role of college knowledge and engagement with faculty and staff for student success. Through a randomized controlled trial intervention, this study leverages the relationship between parents and students to encourage student engagement with faculty and staff during the first year of college. Results of a survey administered to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…In addition to offering new insights into the experiences of first-generation students in college, these findings have important implications for theorizing the relationship between cultural capital and education. While much of the prior literature has examined the role of cultural capital in reproducing social inequality, this study builds on and extends the literature on cultural mobility (Attewell and Lavin 2007;Deutschlander 2019;Domina and Roksa 2012;Jack 2016Jack , 2019. Research on cultural mobility has illuminated how individuals' exposure to higher education can facilitate familiarity with and ability to navigate college.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to offering new insights into the experiences of first-generation students in college, these findings have important implications for theorizing the relationship between cultural capital and education. While much of the prior literature has examined the role of cultural capital in reproducing social inequality, this study builds on and extends the literature on cultural mobility (Attewell and Lavin 2007;Deutschlander 2019;Domina and Roksa 2012;Jack 2016Jack , 2019. Research on cultural mobility has illuminated how individuals' exposure to higher education can facilitate familiarity with and ability to navigate college.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has noted the importance of family support for underrepresented racial/ethnic minority students (Ceja 2006; Dennis et al 2005; Gloria and Castellanos 2003; Guiffrida 2005; Lopez 2001; Rodriguez et al 2003). Moreover, at least one study of low‐income and first‐generation students has reported that parental support is more important for Latinx students than other racial/ethnic groups, including African American students (Deutschlander 2019). How siblings may both directly and indirectly support students from different racial/ethnic backgrounds, including potential differences between Latinx and African American students, deserves careful attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the zoning system is to make it easier to access new admissions services for students around the school, ensure that school-age residents can get an education, and accommodate students' talents and potential [26,27]. It is hoped that the zoning system within a certain radius will reduce the costs and risks of transporting students to school so that parents benefit from the cost and safety of their children on the way to school [28]. The zoning system prioritises prospective new students who come from the environment around the school, with a portion of 50-70%.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do FGCS have differential outcomes, but they also often feel less supported and do not have access to as many college experiences as their counterparts (Benson & Lee, 2020;Jack, 2019;Pascarella et al, 2004). In particular, FGCS are less likely to reach out to academic advisors or other support staff for essential resources and information because they are: 1) unaware of resources, 2) insecure about their lack of cultural knowledge, or 3) do not want to impose on staff (Deutschlander, 2019;Jack, 2019;Lareau, 2015). However, advisors and support staff can make a significant difference in FGCS outcomes (Bassett, 2020;McCallen & Jonson, 2020;Museus & Ravello, 2010;Tobolowsky et al, 2020;Young-Jones, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%